Online security in e-government as an antecedent of cost-effectiveness and quality in business operations (2023)
Purpose The Colombian Government launched an e-government initiative in 2008 to facilitate communication among the government, citizens and organizations. Considering the high level of mistrust of citizens and businesses toward governmental institutions,